Biocompatibility and Pharmacokinetics of Fluticasone-Eluting Sinus Implant in a Rabbit Model. Issue 6 (November 2017) - Patel, Vishal S.; Walgama, Evan; Psaltis, Alkis; Lavigne, Francois; Pletcher, Steven D.; Hwang, Peter H.
Background: A novel, bioabsorbable, fibrinogen-based implant has been developed as a mucosal dressing after endoscopic sinus surgery (ESS). This implant can be formulated with fluticasone propionate (TP) for local elution of corticosteroid to reduce postoperative inflammation and promote mucosal healing. Objective: This study investigated the biocompatibility and pharmacokinetics of the implant in a rabbit model. Methods: Implants with and without TP were placed on both intact and demucosalized maxillary sinuses of 33 New Zealand White rabbits. Sinuses with either intact or denuded bone without implants acted as controls. Histopathologic assessments were carried out at 5, 15, and 28 days. Concentrations of TP in the maxillary sinus mucosa, nasal cavity mucosa, and plasma were measured for up to 44 days. Results: Implants placed on intact mucosa or denuded bone were grossly integrated within 15 days. Minimal foreign body reaction was seen with negligible differences for inflammation, fibrosis, or bone remodeling among controls, sinuses with the implant, or sinuses with the implant plus TP, at all time points. All samples also showed complete or near-complete percentage reepithelialization at 28 days, although the denuded bone controls demonstrated greater percentage reepithelialization at 5 days compared with denuded bone with the implant or implant plus TP (p <0.0001). The maxillary sinus mucosa demonstrated levels of TP of >140 ng/g up to 44 days. Plasma concentrations of TP were generally very low and were undetectable after day 7. Conclusions: The implant and the implant plus TP seemed to be biocompatible in rabbits. The implant plus TP effectively eluted steroid locally over at least 44 days, with negligible plasma concentrations. Further studies are warranted regarding potential therapeutic applications in patients undergoing ESS for chronic rhinosinusitis.